2022
DOI: 10.1007/s12144-022-03650-6
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the relationships among self-ascribed gender traits, social desirability, and ambivalent sexism

Abstract: The stereotypical gender traits used in self-descriptions could contribute to shape ambivalent sexist attitudes toward women, including antipathy toward women who appear to threaten the gender hierarchy (i.e., hostile sexist attitudes) and affection for women who embrace traditional feminine roles (i.e., benevolent sexism). Empirical evidence associates more stereotypically feminine traits with benevolent sexism and masculine traits with hostile sexism but does not offer a clear picture, likely because of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 37 publications
(88 reference statements)
0
1
0
Order By: Relevance
“…Additionally, it included measures regarding women staying at home and not going to work to take care of children when they are ill. It is possible that this scale evoked socially desirable responses, given that previous research has revealed differences in how individuals respond on different sexism measures in terms of benevolent vs. hostile sexism (Agut et al, 2022). This may also explain why adolescents in our sample generally had low scores on professional sexism.…”
Section: Professional Sexism As a Potential Explanation For Unstable ...mentioning
confidence: 84%
“…Additionally, it included measures regarding women staying at home and not going to work to take care of children when they are ill. It is possible that this scale evoked socially desirable responses, given that previous research has revealed differences in how individuals respond on different sexism measures in terms of benevolent vs. hostile sexism (Agut et al, 2022). This may also explain why adolescents in our sample generally had low scores on professional sexism.…”
Section: Professional Sexism As a Potential Explanation For Unstable ...mentioning
confidence: 84%